ANALISIS KEBUTUHAN DAN MINAT PENGGUNAAN PLATFORM PINJAMAN DAN PEMBAYARAN ONLINE PADA APLIKASI ESCETE DI KSP CREDIT UNION BAHTERA SEJAHTERA TEMPAT PELAYANAN KEWAPANTE - Fransiskus Xaverius Muko Sorowutun; Imanuel Wellem; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2026)
The rapid development of information technology has transformed the way financial institutions deliver services, including credit unions. To improve service quality and accessibility for its members, KSP Credit Union Bahtera Sejahtera introduced a digital platform through the ESCETE application, which enables members to conduct loan and payment transactions online. This study aims to analyze the needs and members’ interest in using the online loan and payment platform provided by the ESCETE application at KSP Credit Union Bahtera Sejahtera, Kewapante Service Office. The findings reveal that the ESCETE application significantly facilitates members in conducting financial transactions without visiting the service office. The platform also improves employees’ work efficiency and accelerates service delivery. Members demonstrate a relatively high level of interest in using the application due to its accessibility and time efficiency. However, several challenges remain, including limited digital literacy among some members and unstable internet connectivity. This study concludes that the ESCETE application plays an important role in supporting digital financial services in credit unions. Therefore, continuous socialization and user assistance are necessary to maximize the utilization of the application